New Show Paradigm of Wayang Klithik Wonosoco - I Nyoman Murtana (Institut Seni Indonesia Yogyakarta, 2018)
AbstractWayang Klithik Wonosoco is classified as rare because it is only performedonce a year as a means of bersih desa ritual. However, the show still comeswith a new paradigm. The results of the study show that the wayang KlithikWonosoco Village has undergone a paradigm shift since puppeteer and severalmusicians studied at the Surakarta Kasunanan Palace. This research appliedbasic research method by applying the theory of change to enrich the basicknowledge. The basic understanding of the values of the cultural practices ofwayang shows in the Surakarta Kasunanan Palace is converted to WonosocoVillage after going through an adaptation process. This article is expectedto be an inspiration for the development of science and practice in the fieldof puppet art. The paradigm of Wayang Klithik Wonosoco has changed; as aresult, it becomes new. The changes involve the concepts, methods, forms andstructures of the staging which consists of jejer, babak unjal, paseban jawi,perang gagal, goro-goro, pertapan, perang brubuh, and tancep kayon. Likewisesulukan (puppeteer singing) is enriched with several cengkok sulukan of shadowpuppet and pocapan (monologue) as signs of changing scenes in each pathet.The adaptation process has change the form and structure of Wayang KlithikWonosoco show; it becomes new.Keywords: Wayang Klithik; Wonosoco